Regulatory T Cell Phenotype Related to Cytokine Expression Patterns in Post‐COVID‐19 Pulmonary Fibrosis and Idiopathic Pulmonary Fibrosis - Sara Gangi; Laura Bergantini; Irene Paggi; Marco Spalletti; Paolo Cameli; Elena Bargagli; Miriana d'Alessandro (Immunity, Inflammation and Disease)
ABSTRACT Background Post‐coronavirus disease 19 lung fibrosis (PCLF) shares common immunological abnormalities with idiopathic pulmonary fibrosis (IPF), characterized by an unbalanced cytokine profile being associated with the development of lung fibrosis. The aim of the present study was to analyze and compare the different subsets of CD4‐ and CD8‐T cells, along with specific cytokine expression patterns, in peripheral blood (PB) from patients affected by PCLF and IPF and healthy controls (HCs). Methods One‐hundred patients followed at the Rare Lung Disease Center of Siena University Hospital were enrolled. Eight HCs were recruited. PB samples were collected, and CD4‐ and CD8‐T subsets were analyzed through flow cytometry. Multiplex bead‐based LEGENDplex™ were used for cytokine quantification. Results Higher CD8 percentages were observed in IPF than in HCs and PCLF (p = 0.020 and p = 0.007, respectively). PCLF subgroup showed higher Th‐naïve, Th‐effector, Tc‐naïve, and Tc‐reg percentages than IPF (p < 0.001; p = 0.018; p = 0.005; p = 0.017, respectively). Th‐naïve and Tc‐naïve inversely correlated with Tc‐reg (p < 0.0001, r = −0.61 and p = 0.005, r = −0.39, respectively). Tc‐naïve‐PD1 and Tc‐effector‐PD1 percentages were higher in PCLF than IPF (p < 0.001), while Tfh‐reg and Tfc‐reg were significantly higher in IPF than PCLF (p < 0.001). IL‐4, IL‐2, TNF‐α, and IL‐17A were more expressed in PCLF than IPF (p < 0.001). IL‐8 directly correlated with Tc‐naïve percentages in PCLF (p = 0.018, r = 0.35). Conclusion A variety of immune cells is involved in the development and progression of pulmonary fibrosis confirming an immunological similarity between IPF and PCLF. T‐reg cells play a key role in the worsening of the disease. High cytokine values showed a pro‐fibrotic environment in PCLF patients, suggesting dysregulation of the immune system of these patients. Moreover, the immunological similarity between IPF and PCLF patients suggests that SARS‐CoV2 infection may trigger the activation of biological pathways common with IPF.